Investigating on the supply chain management - Azizi, Amir; Ismail, Napsiah (2005)
In this paper, we review SCM recent articles. Supply chain management (SCM) is the 21st century global operations strategy for achieving organizational competitiveness. Supply chain management has emerged as a critical arena in which firms can find significant cost reduction opportunities giving them a cost advantage over competitors. Also SCM has emerged as an increasingly important approach to improving the performance of logistiks systems. Supply chain management and networks are important fields of study nowadays. SCM is an integrated approach to increase the effectiveness of the logistics chain by improving cooperation between the players in the chain.